Arts-based interventions to improve cognition in older persons with mild cognitive impairment: A systematic review of randomized controlled trials. (23rd August 2021) - Fong, Zhi Hui; Tan, Ser Hong; Mahendran, Rathi; Kua, Ee Heok; Chee, Tji Tjian
Abstract: Objectives: As the global burden of dementia rises, the search for preventive measures such as interventions for mild cognitive impairment (MCI) remains a research priority. While arts-based interventions have demonstrated some success in improving cognitive functioning among older adults and those with dementia, its effectiveness for older persons with MCI remains unexplored. We conducted a systematic review to examine the effects of arts-based interventions on cognition in older persons with MCI. Method: The following databases were searched in November 2019: PubMed, EMBASE, PsycINFO, and CINAHL Plus, supplemented by Google Scholar and ALOIS. Study inclusion criteria were older persons aged ≥ 60 with MCI; arts-based interventions such as dance, drama, music, or visual arts; and randomized controlled trial with cognitive outcome. Database search, study selection, and data extraction were conducted independently by 2 reviewers. Results: Eleven randomized controlled trials examining 13 interventions (817 participants) were identified, of which 4 involved visual arts, 4 dance/movement, 3 music, and 2 storytelling. Significant improvement on at least one cognitive outcome was reported in 10 of the 13 interventions. These included improvements in global cognition (6/7 interventions), learning and memory (5/9), complex attention (4/10), executive functioning (2/6), language (2/3), and perceptual-motor function (1/4). Conclusion: This review found that arts-based interventions can potentially improve various aspects of cognitive functioning in older persons with MCI, although our confidence was dampened by methodological limitations such as the moderate-to-high risk of bias present in studies and heterogeneity in the way MCI was defined. Recommendations for future research are discussed.